Efektivitas Media Pembelajaran Interaktif Lumen5 terhadap Kemampuan Berpikir Kritis Peserta Didik - Netriwati Netriwati; Rosida Rakhmawati Muhammad; Novi Kharesa; Reta Wulandari; Syairadina Putri; Adriansyah Adriansyah; Mifta Arifin (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Field observations indicate that students' critical thinking skills are still lacking. In a public junior high school in Metro City, students' critical thinking skills are relatively low, as evidenced by an average score of 39. This study aims to evaluate the effectiveness of using Lumen5-based interactive learning media in improving students' critical thinking skills. This study used a quasi-experimental methodology with a single-group pretest-posttest design. The study participants consisted of 40 eighth-grade students. The instrument used was a critical thinking skills assessment consisting of four indicators: problem recognition and resolution, analysis, evaluation, and conclusion formulation. The analysis results showed a significant difference between pre-test and post-test scores (p<0.05), indicating an increase in critical thinking skills after using Lumen5. Thus, Lumen5-based interactive learning media has proven effective in improving students' critical thinking skills.